Analysis of the Choice of Transportation Modes from Lhokseumawe City to Medan City Using the Analytical Hierarchy Process Method - Afdal, Muhammad; Muhammad Ridwan, Teuku; Malasyi, Syibral; Savira Elsa, Nanda; Chandra, Yovi (Malikussaleh University, Aceh, Indonesia, 2024)
Interprovincial movement activities from the city of Lhokseumawe to the city of Medan is a busy travel route because land routes connect many cities. Minibusses and buses serve transportation needs across these cities. Travelers tend to choose minibusses because of their convenience, fast travel time, and the excellent level of comfort provided. The bus mode also offers smooth and comfortable travel, making it a popular choice among travelers on the Lhokseumawe to Medan route. This research aims to determine the characteristics and percentage of transportation mode choices by travelers. The approach used is the analytical hierarchy process method. The results of the analysis showed that the percentage of travelers interested in choosing a particular mode resulted in 42% of passengers choosing the Hiace Minibus, 24% choosing the Sempati Star Bus, 20% choosing the Putra Pelangi Bus, and 14% choosing the Kurnia Bus. The criteria that influence the choice of transportation mode are convenience with a percentage of 22%, time with a percentage of 19%, comfort with a percentage of 16%, cost with a percentage of 15%, headway and safety with a percentage of 14%.